Digital peroral pancreatoscopy to determine surgery for patients who have intraductal papillary mucinous neoplasms of the pancreas with mural nodules - Koshita, Shinsuke; Noda, Yutaka; Kanno, Yoshihide; Ogawa, Takahisa; Kusunose, Hiroaki; Sakai, Toshitaka; Yonamine, Keisuke; Miyamoto, Kazuaki; Kozakai, Fumisato; Okano, Haruka; Matsuoka, Yuto; Hosokawa, Kento; Sumiya, Hidehito; Oikawa, Masaya; Tsuchiya, Takashi; Sawai, Takashi; Ito, Kei (Endoscopy International Open, 2024)
Background and study aims Because more than a few patients have intraductal papillary mucinous neoplasms of the pancreas (IPMNs) with mural nodules (MNs) that are benign, clinical plans should be determined by using histocytological specimens especially, for patients with high risk for surgery or with a small MN.Patients and methods This study included 27 patients to evaluate the efficacy of peroral pancreatoscopy using a SpyGlass DS system (POPS-DS) for patients with MN-positive IPMN, mainly focusing on the ability of POPS-DS to detect malignancy.Results Biopsy specimens obtained under POPS-DS guidance could be used for histological evaluation of all patients with MNs in the main pancreatic duct and 67% of the patients with MNs in the branch ducts, whereas fluid specimens collected during POPS-DS could be used for histocytological evaluation for all patients. For the 13 patients who underwent surgery just after POPS-DS, the sensitivity, specificity, and accuracy of POPS-DS to detect malignancy were 89%, 100%, and 92%, respectively. For the 12 patients who underwent surveillance without surgery, the cumulative 3-year progression rates for nine benign IPMNs and three malignant ones determined using POPS-DS were 0% and 100%, respectively. However, the sensitivity of POPS to detect IPMN epithelium in the resection margin was 20%. Only one patient developed procedure-related pancreatitis (mild).Conclusions POPS-DS could be used to accurately detect malignancy in patients with MN-positive IPMN. Therefore, histocytological evaluation using POPS-DS can contribute to selection of patients for whom surgery would be appropriate.
Keywords: Pancreatobiliary (ERCP/PTCD); Pancreatoscopy; Endoscopic ultrasonography; Pancreas; Tissue diagnosis